Levodopa-carbidopa intestinal gel in advanced Parkinson's: Final results of the GLORIA registry. (December 2017) - Antonini, Angelo; Poewe, Werner; Chaudhuri, K. Ray; Jech, Robert; Pickut, Barbara; Pirtošek, Zvezdan; Szasz, Jozsef; Valldeoriola, Francesc; Winkler, Christian; Bergmann, Lars; Yegin, Ashley; Onuk, Koray; et al.
Abstract: Introduction: This registry evaluated the 24-month safety and efficacy of levodopa-carbidopa intestinal gel (LCIG) treatment in advanced Parkinson's disease (PD) patients under routine clinical care. Methods: Motor fluctuations, dyskinesia, non-motor symptoms, quality of life, and safety were evaluated. Observations were fully prospective for treatment-naïve patients (60% of patients) and partially retrospective for patients with ≤12 months of pre-treatment with LCIG (40% of patients). Hours of "On" and "Off" time were assessed with a modified version of the Unified Parkinson's Disease Rating Scale part IV items 32 and 39. Results: Overall, 375 patients were enrolled by 75 movement disorder centers in 18 countries and 258 patients completed the registry. At 24 months LCIG treatment led to significant reductions from baseline in "Off" time (hours/day) (mean ± SD = −4.1 ± 3.5, P < 0.001), "On" time with dyskinesia (hours/day) (−1.1 ± 4.8, P = 0.006), Non-Motor Symptom Scale total (−16.7 ± 43.2, P < 0.001) and individual domains scores, and Parkinson's Disease Questionnaire-8 item total score (−7.1 ± 21.0, P < 0.001). Adverse events deemed to have a possible/probable causal relationship to treatment drug/device were reported in 194 (54%) patients; the most frequently reported were decreased weight (6.7%), device related infections (5.9%), device dislocations (4.8%), device issues (4.8%), and polyneuropathy (4.5%). Conclusions: LCIG treatment led to sustained improvements in motor fluctuations, non-motor symptoms particularly sleep/fatigue, mood/cognition and gastrointestinal domains, as well as quality of life in advanced PD patients over 24 months. Safety events were consistent with the established safety profile of LCIG. Highlights: Long-term registry of LCIG treatment in patients with advanced Parkinson's disease. LCIG was delivered over 24 months in a routine clinical care setting. LCIG treatment reduced "Off" time and dyskinesia time over 2 years. LCIG treatment improved non-motor symptoms and quality of life over 2 years. Adverse drug reactions were consistent with the established safety profile of LCIG.